Relationship Between CarotidIntima-Media Thickness and Silent Cerebral Infarction in Japanese Subjects With Type 2 Diabetes - Nomura, Kazuhiro (American Diabetes Association, 2010)
OBJECTIVE: We examined the relationship between intima-media thickness of common carotid artery (CCA-IMT) and silent cerebral infarction (SCI) with the magnetic resonance imaging (MRI) study in Japanese subjects with type 2 diabetes. RESEARCH DESIGN AND METHODS: The brain MRI study and the carotid ultrasonography were performed in a total of 217 consecutive Japanese subjects with type 2 diabetes. Various risk factors for SCI were examined using multiple logistic analyses. RESULTS: The SCI was found in 60.4% of the diabetic subjects. In the diabetic subjects, age, systolic blood pressure (SBP), pulse wave velocity, and CCA-IMT were significantly higher in the subjects with SCI than in those without it. Multiple logistic analyses indicated that age, SBP, and CCA-IMT were significant and independent risk factors of SCI in the diabetic subjects. CONCLUSIONS: CCA-IMT, but not pulse wave velocity, was independently associated with SCI in Japanese subjects with type 2 diabetes.